Creating spaces for change: Engaging civil society to harness change in criminal justice practice. (December 2017) - McCulloch, Trish; Smith, Mark
In a context of neoliberal penality, crime is falling yet prison populations continue to rise. Governments profess to recognise the problem yet have had little impact on underlying trends in criminal justice practice. This article reports on a Scottish initiative to try and disrupt this cycle through broadening the base for deliberation upon justice matters to include civil society. In so doing, we sought to build upon an emerging civic engagement evident in the wake of the 2014 Independence Referendum. Our premise was that to effect change requires that we look beyond policy fixes to the values and the socio-cultural drivers that take practice in particular directions. We conclude with a reflection on the obstacles to change.